Exogent Factors at PT. Metro Taruna Jakarta That Affect Employess Performance - Connie Chairunnisa; M Iqbal Jaelani (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the effect of training and work discipline as exogenous factors on employee performance at PT Metro Taruna Jakarta. This study used survey method with 82 respondents as a sample. The data analysis and process techniques used are validity, reliability, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, simultaneous test, coefficient test, and correlation coefficient of determination.